The Role of E-Governance On Corruption in The Mena Region: A Panel Data Analysis - abdelwareth, Doaa (AUC Knowledge Fountain, 2023)
This study aims to understand the role of e-governance on corruption in Middle East and North African (MENA) countries. The study also links the adoption of e-governance to the promotion of sustainable development. The panel data of 17 MENA countries were collected from various secondary sources from 2003 to 2020. This study's empirical result was estimated using the Generalized Method of Moments econometric approach. This study has achieved four objectives by using the different proxies of e-government, namely the human capital index (HCI), the online service index (OSI), the e-participation index (EPI), and the e- government development index (EGDI), for the control of corruption. The time-series regression model proves the uni-directional causality between the e-governance proxies and corruption. The long dynamic empirical results show that the EGDI, EPI, and OSI significantly decline corruption in the MENA region. At the same time, HCI has an insignificant association with the control of corruption. Based on the results, the study recommends the utilization of information and communication technology (ICT) in the relevant government sectors to control corruption.